Is thoracic facet joint arthritis over-reported? It’s time to review CT grading parameters - An analytical cross-sectional study - Tiwari, Punit; Kaur, Harmeet; Jha, Vivek (Indian Journal of Radiology and Imaging, 2020)
Background: In the absence of any exclusive classification for dorsal FJA, there is a lot of confusion while labelling grade 1 FJA in thoracic spine based on decreased FJ space. Purpose: The purpose of this study was to know the facet joint space measurements in thoracic spine of asymptomatic and symptomatic participants and to comment whether the lower cut-off of 2 mm used in lumbar FJA classification can be safely applied in thoracic spine too. Materials and Methods: This cross-sectional study was done from December 1, 2018 to November 30, 2019. Patients above 18 years of age in this study who underwent CT thorax for causes unrelated to dorsal spinal pain were included. IBM SPSS Statistics v 26 was used for statistical analysis. Results: We measured and analysed 1512 thoracic facet joints in 63 patients (30 females and 33 males) in both axial and sagittal plane on CT scan. Mean age of the entire sample was 59.19 ± 15.19 years, ranging from 33 to 97 years and a standard error of mean 1.365 years. Overall mean thoracic facet joint space was measured to be 1.270 mm ± 0.3416 mm, ranging from 0 to 3.1 mm and a standard error of mean 0.0088 mm and a variance of 0.117 mm. The median was 1.300 mm while mode was 1.1 mm. Conclusion: The popular lumbar FJA classification by Weishupt et al. cannot be applied in its present form in thoracic spine, without the modification in parameters of grade 1 FJA. The lower cut-off of normal thoracic facet joint space probably lies around 1 mm. MeSH Terms: Zygapophyseal joints, dorsal, thoracic, facet joint, arthritis, classification
Keywords: Dorsal; facet joint arthritis; facet joint space; measurements; thoracic; width